Report on the 2007 International Workshop on Human Papillomaviruses and Consensus Recommendations for cervical Cancer Prevention - Grce, Magdalena; Davies, Philip; Arbyn, Marc; Anttila, Ahti; Grubišić, Goran; Kardum-Skelin, Ika; Herbert, Amanda; Jordan, Joseph; Karsa von, Lawrence (Central European Journal of Public Health, 2008)
National and international experts in cervical cancer prevention met at the International Workshop on Human Papillomaviruses and Consensus Recommendations for Cervical Cancer Prevention to review the current evidence and assess the potential for improvement in cervical cancer prevention and to develop plans for implementation of cervical cancer prevention programmes in Croatia. Key recommendations were developed and adopted during the course of the meeting. The process of bringing national experts together with internationally recognized experts in an open forum for the development of consensus recommendations could serve as a model for other countries seeking to implement or improve cervical cancer prevention programmes.
Keywords: Uterine Cervical Neoplasms; dysplazie děložního hrdla; nádory děložního čípku; vakcíny proti papilomavirům; Papillomavirus Vaccines; Mass Screening; Croatia; Chorvatsko; plošný screening; European Union; Practice Guidelines as Topic; Evropská unie; Uterine Cervical Dysplasia; směrnice pro lékařskou praxi jako téma